Survey of Micro, Small, and Medium Enterprises in Agri-Food Value Chains: Network-Based Recruitment Approach in Uganda - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The datasets and questionnaires included in this package are derived from the second phase of the International Food Policy Research Institute (IFPRI) project titled "Digital Financial Services Adoption among Small and Medium Enterprises (SMEs) in the Midstream of Agricultural Value Chains." This project focused on midstream actors within the arabica coffee and soybean value chains in Uganda, utilizing tailored surveys to assess their financial capabilities and constraints. The surveys were conducted in May and June 2023 across the Mbale, Kasese, and Lira districts. The data collection was carried out iteratively to gather information about intermediary actors at various stages of the agri-food value chain. In randomly selected villages within the primary study districts, a small group of farmers participated in a brief survey to identify intermediary actors to whom they had sold commodities in the past 30 days. The identified intermediary actors were then contacted and interviewed using a comprehensive intermediary actor survey. In total, 433 coffee farmers and 247 soybean farmers were interviewed in Uganda. The midstream actor sample for the coffee value chain includes 1,401 traders, 111 processors, 334 wholesalers, and 16 aggregators. For the soybean value chain, the sample consists of 507 traders, 2 processors, 280 wholesalers, 9 storage facilities, and 37 aggregators.